Degradable Magnetic Composites for Minimally Invasive Interventions: Device Fabrication, Targeted Drug Delivery, and Cytotoxicity Tests. Issue 3 (25th November 2015) - Peters, Christian; Hoop, Marcus; Pané, Salvador; Nelson, Bradley J.; Hierold, Christofer
Abstract : Superparamagnetic nanoparticles and a functional, degradable polymer matrix based on poly(ethylene glycol) are combined to enable fully degradable magnetic microdevices for minimally invasive biomedical applications. A bioinspired helical microrobot platform mimicking Escherichia coli bacteria is fabricated and actuated using weak rotating magnetic fields. Locomotion based on corkscrew propulsion, targeted drug delivery, and low‐degradation‐product cytotoxicity are demonstrated.